DNA methylation changes induced by prenatal toxic metal exposure: An overview of epidemiological evidence. Issue 1 (6th October 2021) - Vaiserman, Alexander; Lushchak, Oleh
Abstract: Accumulating evidence suggests that exposure to unfavorable conditions early in life can substantially contribute to the risk of chronic disorders later in life ('developmental programming' phenomenon). The mechanistic basis for this phenomenon remains poorly understood so far, although epigenetic mechanisms such as DNA methylation, histone modifications and microRNA-mediated gene regulation apparently play a crucial role. The key role of epigenetic modifications triggered by unfavorable environmental cues during sensitive developmental periods in linking adverse early-life events to later-life health outcomes is evident from a large body of studies, including methylome-wide association studies and research of candidate genes. Toxic metals (TMs), such as heavy metals, including lead, chromium, cadmium, arsenic, mercury, etc., are among environmental contaminants currently most significantly impacting human health status. Since TMs can cross the placental barrier and accumulate in fetal tissues, exposure to high doses of these xenobiotics early in development is considered to be among important factors contributing to the developmental programming of adult-life diseases in modern societies. In this mini-review, we summarize epidemiological findings indicating that prenatal TM exposure can induce epigenetic dysregulation, thereby potentially affecting adult health outcomes.